Development of spirometric reference equations for children living at high altitude (2020)
This study was aimed to provide locally derived spirometric equations from a population of healthy children residing in Bogota, Colombia, a high‐altitude city. Healthy children aged more than 6 years up to less than 18 years underwent spirometry from January 2017 to January 2018, following the recommendations made by the American Thoracic Society/European Respiratory Society (ATS/ERS) Task Force. We performed stepwise multiple regression analyses to predict each spirometric parameter. We also performed extensive residual analyses comparing the measured values with those calculated with our new spirometric equations and with other commonly used equations. Predictive equations for each spirometric variable were derived from 326 spirometric tests (149 boys, 177 girls). Our newly derived spirometric equations provided the minimum of median of prediction error for almost all spirometric indices measured. We recommend the newly developed spirometric equations for assessing the ventilatory function of children living in Bogota, Colombia.